2017
DOI: 10.5902/2179769226442
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à dor musculoesquelética em estudantes de enfermagem

Abstract: RESUMO: Objetivo: verificar a prevalência e fatores associados à dor musculoesquelética em estudantes de enfermagem. Método: estudo transversal, realizado em 2014, com 149 estudantes de enfermagem de uma universidade pública no Sul do Brasil. Utilizou-se questionário com questões sociodemográficas, acadêmicas, de saúde e a versão brasileira do Standardized Nordic Questionnaire. A associação foi estimada pela Odds Ratio e seus intervalos de confiança. Resultados: nos últimos sete dias, predominou dor musculoesq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
4
0
5
Order By: Relevance
“…There is also mention of health teams that are not welcoming of students, leading to conflictive relationships, which is associated with the suffering of the students. 16,72,73 In the educational process there are, at least, two actors: a student and a professor. Therefore, the studies in this revision also highlighted the perspective of the professors regarding the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…There is also mention of health teams that are not welcoming of students, leading to conflictive relationships, which is associated with the suffering of the students. 16,72,73 In the educational process there are, at least, two actors: a student and a professor. Therefore, the studies in this revision also highlighted the perspective of the professors regarding the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, studies with the present proposal can help substantiate the development of prevention mechanisms, which undergraduate courses can implement, and encourage students to exercise health promotion measures. 16 It is noteworthy that the present article was developed amid the COVID-19 pandemic, a disease caused by the SARS-CoV-2 virus, and that no studies were found that analyzed the association between the variables CP, anxiety, and depressive symptoms in university students. This further justifies the importance of this study, considering that its results will contribute to shedding more light on the situation that these students are experiencing in the current context.…”
Section: Introductionmentioning
confidence: 95%
“…In this context, leisure activities are fundamental for health promotion, as they favor relaxation and relief of tensions resulting from the students' academic daily life, 28 which helps in the prevention of MP. Thus, it becomes important to provide spaces for the students in the academic environment that favor the relief of tensions by means of leisure activities, such as conversation circles, promotion of physical activities and cultural spaces, among others.…”
Section: /14mentioning
confidence: 99%